Metode Charging Constant Current Constant Voltage Baterai Li-Po - Dany Mufty, Wasith; Khoirunnisaa, Alfi Zuhriya (Fakultas Teknik UMRI, 2026)
The use of renewable energy has experienced significant developments, especially solar panel technology. Due to the unstable nature of solar energy sources, an energy storage system is needed to maintain the continuity of power supply in the form of batteries. One type of battery is the Lithium Polymer (Li-Po) battery, which is often used because it has a high energy density and good work efficiency. However, over time the battery capacity will decrease so it needs to be charged. When charging, there is a risk of overcharging, so the Constant Current Constant Voltage (CC-CV) charging method is needed. This method is usually combined with a Proportional-Integral (PI) controller to regulate the Buck converter output through signal adjustments so that the current and voltage match the desired values. The use of the combination of the CC-CV method and PI control allows real-time regulation of charging parameters based on the battery's State of Charge (SoC) conditions, thereby extending battery life and improving the safety of solar panel-based energy storage systems.